1993
DOI: 10.1007/bf00298728
|View full text |Cite
|
Sign up to set email alerts
|

Aminoalkylbisphosphonates, potent inhibitors of bone resorption, induce a prolonged stimulation of histamine synthesis and increase macrophages, granulocytes, and osteoclasts in vivo

Abstract: Aminoalkyl derivatives of bisphosphonates are potent inhibitors of bone resorption. A single I.P. injection of 4-amino-1-hydroxybutylidene-1,1-bis-phosphonate (AHBuBP) induced a prolonged enhancement of histidine decarboxylase (HDC) activity in the bone marrow, spleen, lung, and liver of mice and resulted in an increase in histamine. The induction of HDC by the agent was dose dependent (16-80 mumol/kg) and peaked 3-4 days after its injection (40 mumol/kg). Repeated S.C. injections of smaller doses of AHBuBP (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
60
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 30 publications
10
60
1
Order By: Relevance
“…In the first situation, the inflammatory reaction was mild, and its hallmarks were bone marrow fibrosis and moderate inflammatory cell infiltration without vascular change. The observed stimulation of osteoclast recruitment despite ongoing bisphosphonate treatment may result from this inflammatory state; accordingly, Endo et al reported that NBP injections in mice increased marrow macrophage and osteoclast numbers [22]. Other Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In the first situation, the inflammatory reaction was mild, and its hallmarks were bone marrow fibrosis and moderate inflammatory cell infiltration without vascular change. The observed stimulation of osteoclast recruitment despite ongoing bisphosphonate treatment may result from this inflammatory state; accordingly, Endo et al reported that NBP injections in mice increased marrow macrophage and osteoclast numbers [22]. Other Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Nitrogen-containing bisphosphonates (such as alendronate) induce various inflammatory reactions via interleukin dependent mechanisms. [27][28][29][30] Bisphosphonate-induced inflammation exacerbates pathologic conditions such as arthritis 31 and atherosclerosis. 32 Blockage of matrix metalloproteinases improves anterior cruciate graft healing in the bone tunnels.…”
Section: Discussionmentioning
confidence: 99%
“…Among these derivatives, aminobisphosphonates (aminoBPs) are particularly potent. We have reported that aminoBPs with a free amino group in their molecule, when injected into mice, enhanced the activity of histidine decarboxylase (HDC), the enzyme forming histamine, in the bone marrow, spleen, lung and liver (Endo et al, 1993). However, non-aminoBPs showed no such activity.…”
Section: Introductionmentioning
confidence: 99%